Analisis Dampak Cyberbullying pada Kesehatan Choi Jin-Ri (Sulli) Artis Korea dan Film Dokumenter Terakhirnya - Dwi Kurniawati; Khadijah Khadijah; Yasinta Citra Dewi Kurniasari; Doan Widhiandono (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The purpose of this research is to find out the impact of cyberbullying on the health of Korean artist Choi Jinri (Sulli). In this research method, we use a qualitative method or descriptive method using the note-taking technique, where we as researchers carry out an analysis by watching via the Netflix channel. Netflix released a documentary film in memory of the idol entitled "Persona Sulli." This film consists of two parts, namely the first entitled "4: Clean Island" and the second entitled "Dear Jinri". This film will be the late Sulli's final work that fans can watch. From the results of this analysis, we conclude that the impact of cyberbullying not only disrupts the victim's daily activities but can also have a big impact on the victim's health and mental health.